Effect Of Anagram Games In Enriching Stdents’ Vocabulary At Smp Advent 2 Medan - Madina, Madina; Tamba, Novika (CV. ITTC INDONESIA, 2023)
This study aims to see how effective the anagram game technique is in enriching the vocabulary of Grade VIII students at SMP Advent 2 Medan at the school in 2023., this research is a experimental conducted on two classes where one class consists of 23 students, so a total of 46 students were taken and divided into two groups, namely the experimental group and the control group. Data collection was carried out through pretest, treatment and post test objectively.In this study using data collection techniques with the SPSS formula in which there are 3 analytical techniques used 1. descriptive analysis, 2. homogeneity test, 3 normality test.based on this research the test results have been obtained with an average pretest score of 65.65, and an average post test score of 79.57, so you can see a significant difference in the game experiment, between the pretest and post-test, t(df=23) = 0.715 at p = 0.000 lower than 0.05. succeeded with 100 percent success in directing students to acquire new vocabulary quickly.. Thus the use of this anagram game is one way that can be used by teachers as a learning guide in enriching student vocabulary.